Study on the dynamics characteristics and screening performance of the disc spring vibration screen - Jiacheng Zhou; Libin Zhang; Longchao Cao; Junjie Tang; Kuanmin Mao; Lianqing Yu (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
The disc spring system is applied to the vibration screen, which can effectively reduce the exciting force and improve screening capacity. In this work, the dynamic characteristics and screening performance of the disc spring vibration screen are studied. The modal simulation and experimental results show that the model vibration direction at first natural frequency is consistent with the working direction of the vibration screen. Moreover, the trajectory analysis and discrete element screening simulation prove that the disc spring vibration screen has better screening performance than the coil spring vibration screen. Eventually, by comparing required exciting force under the same amplitude, fatigue life of the spindle bearing, and energy consumption between the coil spring and disc spring vibration screen, it can be found that disc spring vibration screen has better mechanical properties, higher reliability, and lower energy consumption.